Board gender diversity effect to various earnings management estimation models / Iylia Dayana Mohamed Izwan ... [et al.] - Mohamed Izwan, Iylia Dayana; Muhammad, Muhammad Ahmad Dost; Zakaria, Nor Balkish; Mohamad, Maslinawati; Ahmad, Maizatul Akhmam (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study examines the impact of board gender diversity across earnings management techniques. We employ the Generalised Method of Moments (GMM) technique to examine data gathered from Malaysian manufacturing companies' annual reports on Bursa Malaysia between 2016 and 2021. Our analysis is based on a sample of 1,290 firm-year observations. The presence of the female board was significantly influenced by the accrual earnings shown by Modified Jones, Kothari's model, and abnormal production cost earnings management. However, when the board consists of 30% women, only abnormal production cost earnings management, cash flow from operations and discretionary expenses were considered significant. The results of this study provide valuable insights to authorities, managers, and investors on the representation of women on corporate boards, as highlighted in the MCCG 2021 guidelines as a means of enhancing the implementation of earnings management.